2017
DOI: 10.15406/aovs.2017.06.00184
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Central Serous Chorioretinopathy (Csc) Using Diclofenac through Different Routes of Administration, a Comparative Study

Abstract: Purpose: To evaluate the effect of diclofenac nonsteroidal antiinflammatory drug (NSAID) in the treatment of acute central serous chorioretinopathy (CSC) by different routes of administration and compare the results with control patients. Introduction:Central serous chorioretinopathy (CSC) is an idiopathic disorder characterized by a serous detachment of the neurosensory retina at the macula, which is caused by active retinal pigment epithelial (RPE) leakage. Although the exact pathophysiology of CSC has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…11 Patient was first treated with topical and oral NSAID which works by decreasing prostaglandin production by inhibit the production of cyclooxygen enzyme (COX), an agent responsible for vasodilatation and increasing blood vessel permeability. A study conducted by Khan et al 21 found that the use of topical NSAID improved CMT and visual acuity up to 30 th day after treatment. However, in our case, patient's condition did not improve after NSAID administration.…”
Section: Discussionmentioning
confidence: 97%
“…11 Patient was first treated with topical and oral NSAID which works by decreasing prostaglandin production by inhibit the production of cyclooxygen enzyme (COX), an agent responsible for vasodilatation and increasing blood vessel permeability. A study conducted by Khan et al 21 found that the use of topical NSAID improved CMT and visual acuity up to 30 th day after treatment. However, in our case, patient's condition did not improve after NSAID administration.…”
Section: Discussionmentioning
confidence: 97%